Responding to a Potentially Disruptive Technology: How Big Pharma Embraced Biotechnology. (August 2018) - Birkinshaw, Julian; Visnjic, Ivanka; Best, Simon
How do incumbent firms respond over time to a potentially disruptive technology? This article documents the strategies of 12 large pharmaceutical firms over 25 years as they addressed the opportunity/threat of biotechnology. All showed awareness of biotechnology's potential, but their response profiles varied dramatically in terms of timing (early/late) and focus (external/internal). Late movers mostly made large acquisitions to "catch up, " but early movers maintained their lead in terms of biotechnology-based drug sales and profitability, and those with a more "open" response profile performed better. This response involves a three-step process: building awareness (sensing), building capability (responding), and building commitment (scaling).